2004
DOI: 10.1063/1.1781615
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and vibrational properties of amino acids

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 24 publications
3
29
2
Order By: Relevance
“…HF/aug-cc-pVDZ values are very close to the HF/POL-Sadlej ones reported by Hansen et al [11]. Our correlated values are somewhat smaller than those reported by Tulip and Clark on alanine, isoleucine, leucine and valine [12], while they well correlate with the DFT-LB94/QZ4p polarizabilities of the amino acid residues reported by Smart et al [13]. We consider the reported values as the most accurate dipole polarizability data of the present amino acids to date.…”
Section: Electronic Polarizabilitiessupporting
confidence: 87%
See 1 more Smart Citation
“…HF/aug-cc-pVDZ values are very close to the HF/POL-Sadlej ones reported by Hansen et al [11]. Our correlated values are somewhat smaller than those reported by Tulip and Clark on alanine, isoleucine, leucine and valine [12], while they well correlate with the DFT-LB94/QZ4p polarizabilities of the amino acid residues reported by Smart et al [13]. We consider the reported values as the most accurate dipole polarizability data of the present amino acids to date.…”
Section: Electronic Polarizabilitiessupporting
confidence: 87%
“…Hansen et al [11] reported the frequency-dependent polarizabilities of the twenty essential amino acids calculated by HF and point dipole interaction (PDI) models. Tulip and Clark [12] calculated…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Up to now, some work dealt with the THz spectrum of L-alanine only in terms of experiment [21][22][23]. Others, using a combination of experiment and simulation, only focused on the spectral range in 0.5-3.1 THz [24] or calculated the THz spectrum in a single molecular mode [25]. Through these previous researches, we find that the origins of the measured spectral peaks of L-alanine in the range of 0.5-4.0 THz are still not clearly explained, especially the peaks located at 3.11 and 3.33 THz.…”
Section: Introductionmentioning
confidence: 99%
“…Among amino acids, of particular interest is L-alanine due to its simple molecular structure. Much work has been carried out on the spectral properties of L-alanine, including Raman scattering (25-175 cm −1 ) [19], farinfrared absorption spectra (20-600 cm −1 ) [20], and THz absorption spectra [21][22][23][24][25]. Up to now, some work dealt with the THz spectrum of L-alanine only in terms of experiment [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some progress has been made in understanding the anisotropy of the polarizability for molecules and molecular crystals [18][19][20][21] and for the dielectric and vibrational properties of some of the simpler amino acid molecules. 22 Very recently, an ab initio dynamics study has been carried out for the undoped polymer PPV. 23 In this work we present a first-principles investigation of the dynamical properties of the conducting polymers PANi and PPyV.…”
Section: Introductionmentioning
confidence: 99%